Environmental Change Threatens Freshwater Insect Communities in Northwest Africa: A Meta-Analysis - Kaczmarek, Nils; Schäfer, Ralf B.; Berger, Elisabeth (Frontiers in Environmental Science, 2021)
A climatic shift from temperate to arid conditions is predicted for Northwest Africa. Water temperature, salinity, and river intermittency are likely to increase, which may impact freshwater communities, ecosystem functioning, and related ecosystem services. Quantitative data and information on the impact of climate change on insect communities (e.g., richness, taxonomic and trait composition) are still scarce for Northwest Africa. In this study, we extracted information on freshwater insect occurrence and environmental variables in Northwest Africa from the results of a literature search to study potential consequences of changing climatic conditions for these communities. Our data set covered 96 families in 165 sites in Morocco and Algeria. We quantified the impact of several explanatory variables (climate, altitude, water temperature, conductivity, intermittency, flow, aridity, dams, and land cover) on richness, taxonomic and functional trait composition using negative binomial regression models and constrained ordination. Family richness in arid sites was on average 37 % lower than in temperate sites in association with flow, river regulation, cropland extent, conductivity, altitude, and water temperature. With 36 % of the studied temperate sites predicted to turn arid by the end of the century, a loss of insect families can be predicted for Northwest Africa, mainly affecting species adapted to temperate environments. Resistance and resilience traits such as small body size, aerial dispersal, and air breathing promote survival in arid climates. Future research should report insect occurrences on species level to allow for better predictions on climate change effects.